2010
DOI: 10.1017/s1121189x00000877
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model to allocate frequent service users of community-based Mental Health Services to different packages of care

Abstract: SummaryAim– To develop predictive models to allocate patients into frequent and low service users groups within the Italian Community-based Mental Health Services (CMHSs). To allocate frequent users to different packages of care, identifing the costs of these packages.Methods– Socio-demographic and clinical data and GAF scores at baseline were collected for 1250 users attending five CMHSs. All psychiatric contacts made by these patients during six months were recorded. A logistic regression identified frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Care packages have been defined as the cluster of services, based on carefully constructed components, provided to each patient in different settings by different professionals in a specific time frame (Grigoletti et al, 2010; National Health Service (NHS) Executive, 1997). As described elsewhere (Lora et al, 2007), a previous analysis identified five mutually exclusive packages for individual patients in the course of 1 year:…”
Section: Discussionmentioning
confidence: 99%
“…Care packages have been defined as the cluster of services, based on carefully constructed components, provided to each patient in different settings by different professionals in a specific time frame (Grigoletti et al, 2010; National Health Service (NHS) Executive, 1997). As described elsewhere (Lora et al, 2007), a previous analysis identified five mutually exclusive packages for individual patients in the course of 1 year:…”
Section: Discussionmentioning
confidence: 99%
“…The decision to seek help for mental disorders is a complex process that involves personal socio-demographic characteristics, culturally mediated interpretations of symptoms, availability of healthcare services, economic and socio-structural factors, and healthcare service organization [ 22 ]. A number of healthcare service utilization models exist [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ], but most studies of healthcare service utilization for mental health reasons have used the behavioral model developed by Andersen in the 1960s [ 15 , 16 , 17 , 18 , 30 , 31 , 32 ]. This model conceptualized healthcare service utilization as a function of individuals’ predisposing, enabling, and needs characteristics [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, new Belgian guidelines advise FACT as the standard mode of treatment delivery for SMI patients (SCEM Conference Services, 2011). In Italy, clinical principles comparable to those underlying FACT (outpatient treatment and case management) are guiding treatment delivery (Lora et al 2007, Grigoletti et al 2010). …”
Section: Introductionmentioning
confidence: 99%